Shame and self-acceptance in continued flux: Qualitative study of the embodied experience of significant weight loss and removal of resultant excess skin by plastic surgery. (September 2013) - Smith, Fran; Farrants, Jacqui R
This study explored the embodied experience of body change using a qualitative design. Eight previous plastic surgery patients of a London hospital took part in in-depth, semi-structured interviews 1 year post a plastic surgery procedure to remove excess skin around their abdomen, resulting from weight loss. Participant interviews were analysed using Interpretative Phenomenological Analysis. Two sub-themes titled 'Shame of the hidden body' and 'Lack of acceptance; the future focused body' are presented in this article. Findings are considered in relation to theories of 'Body Shame' and in the current cultural context.